Speaking cooperation, acting competition: Supply-side subsidies and private schools in socioeconomically disadvantaged contexts in Buenos Aires - Mauro C. Moschetti; Carolina Snaider (Arizona State University, 2019)
Few studies have explored how schools respond to competition in socially embedded education quasi-markets. This study focuses on how state-subsidized privately-run low-fee schools (S-LFPSs) compete with free public schools in some of the poorest neighborhoods of the City of Buenos Aires. In particular, we explore how S-LFPSs follow different logics of action to attract (and shape) enrollment profiting from their extended autonomy and some regulatory gaps. We applied discourse analysis on data from eight months of ethnographic case study research in nine S-LFPSs. Student selection and operational changes (e.g., increasing the student/teacher ratio) prevail over academic and curricular changes. Selection is operated by means of aptitude tests and screening interviews, and other symbolic artifacts aimed at signaling differences with state-run schools and the potential fit between schools and families. We present a heuristic typology of the different logics of action systematizing the schools' responses as their leading orientations toward the competitive environment. We suggest that policy inconsistencies and deficient governmental oversight tilt the field against state-run schools. Rather than ensuring equality of educational opportunity, the policy contributes to shape and deepen a highly segregated and inequitable educational landscape.